Podnikatelský záměr - přeměna obchodní společnosti - Mandovcová, Kateřina (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Předmětem diplomové práce je analýza podnikatelského záměru stavební společnosti, návrh strategie a komparace variant realizace navržené strategie. Komparace bude v práci provedena z pohledu ekonomického, právního a daňového. Přínos práce by měl být jednak ve vytvoření teoretického základu pro podniky řešící obecně analýzu podnikatelského plánu a návrh další strategie podniku, zejména by však v praktické části měl vybranému podniku pomoci s jeho aktuálním podnikatelským záměrem.

The main goal of this thesis is a building societies bussiness plan analysis, strategy suggestion and comparison of realization options of suggested strategy. The comparison is going to be done from economical, jurisdictional and taxative points of view. Dissertation will contribute to create theoretical basis for enterprises, which are dealing with basic analysis of bussiness plan, and then the contribution will contain upcoming strategies, especially in practical part of the thesis. This practical part may greatly help to eneterprises with recent bussiness plan.
Business Plan - Transformation of Business Company
Keywords: Podnikatelský záměr; podnikatelský plán; strategie podniku; přeměna podniku; bussiness plan; strategy of an enterprise; enterprise conversion